Perceptions of impoverished mothers on positive and negative monitoring practices - Palheta da Silva, Ísis de Cássia; Cota, Steffanie Brito; Leal Soares Ramos, Edson Marcos; Ramos Pontes, Fernando Augusto; dos Santos, Thamyris Maués; da Costa Silva, Simone Souza (Interação em Psicologia, 2022)
The objective of this study was to describe the perception of poor mothers living in the metropolitan region of Belém-PA, about their practices of positive and negative monitoring. Participated in this study 13 guardians who, in addition to responding to the following quantitative instruments: ISD (sociodemographic inventory), IPF (family poverty index) and IEP (parenting styles inventory), participated in a focus group. Participants were divided according to the level of family poverty into two groups, namely, more and less poor. The data collection stages were respectively carried out in Social Assistance Reference Centers (Centros de Referência em Assistência Social - CRAS), located in peripheral areas of the city of Belém-PA and in classrooms of the Behavior Theory and Research Nucleus (NTPC). The qualitative data analysis confirmed the relationship between higher levels of deprivation and higher probabilities of negative monitoring. The results point to the challenges and demands of the vulnerability context that weaken the ability to exercise positive parenting.